Pemanfaatan kain flannel untuk produk pembelajaran di PAUD HI BKB Kemas Kutilang, Desa Kadugenep - Widyastuti, Putri Anggraeni; Fuad, Ahmad; Stevanny, Stevanny (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
PAUD HI BKB Kemas Kutilang in Kadugenep Village (as a village that produces klakat and bags) has not utilized local materials in teaching and learning activities. Therefore, a Japanese-style handheld fan learning product made from plastic was designed by applying the technique of plaiting pieces of flannel fabric. The problem is to determine the color of the flannel fabric to improve the creativity process of the PAUD students. The purpose and benefit is to identify the color of flannel in solving the problem to develop the creativity process for PAUD HI BKB Kemas Kutilang students. The research method used was qualitative with participatory design approach and material exploration. As a result, rainbow-themed colors, light brown and dark brown on flannel fabric, graded from dark to light colors to represent cheerful characteristics, were used in the design of this learning product. In conclusion, the rainbow theme colors have a cheerful character adapted to the target of learning products, namely PAUD HI BKB Kemas Kutilang students, in order to increase the interest and creativity of these students in carrying out learning activities.